PENGGUNAAN KARTU KREDIT DAN PERILAKU BELANJA KOMPULSIF: DAMPAKNYA PADA RISIKO GAGAL BAYAR - Sumarto .; Andi Subroto; Adil Arianto (Jurnal Manajemen Pemasaran, 2011)
Realization of Non-Performing Loans (NPL) credit cards in the period 2007 to 2010 has experienced a rising trend. Anincrease of NPLhave been caused by the use of credit cards and compulsive buying. The purpose of this study was to determine the effect of credit card use and compulsive buying against default risk. Variables consisted of: the use of credit cards (independent variable), compulsive buying, and default risk (dependent variable). By using the method of sampling purpose, the respondents of this study is the user's credit card Bank X in Surabaya, and the number of samples are 120 respondents. The analytical method used is descriptive analysis and inferential statistical approach using SEM Approach. Researchconclusionsare: the use of creditcards havesignificant effect on compulsive buying, the use ofcreditcards have no significant effect on default risk andcompulsive buyingsignificantly influence to default risk.